New records of the rufous-faced crake, laterallus xenopterus (Gruiformes: Rallidae) in Brazil and observations about its habitat - De Castro, Victor Gonçalves; De Jesus, Shayana [UNESP]; Santos, Danilo Wilson da Mota; Silva, Luciano de Faria (My University, 2014)
The Rufous-faced Crake, Laterallus xenopterus, is a bird that is rarely spotted at Paraguay, central Brazil, and central Bolivia. There are known species records at the Brazilian states of Distrito Federal, São Paulo, and Minas Gerais. Here, we provide information about new areas of occurrence for this species in Brazil and detailed observations of its habitats. In October 2012, two individuals were registered in the municipality of Cristalina, state of Goiás. In December 2012, the species was found in a new locality of Distrito Federal and at the municipality of Patrocínio, Minas Gerais. In February 2013, a new record for this species was obtained in the municipality of Itiquira, Mato Grosso. In all occasions, the bird was spotted in humid environments, which were characterized by the presence of grass and a thin water layer.
Keywords: Cerrado; Distribution; Grasslands; Rail; Range extension